Brain endurance training improves endurance and cognitive performance in road cyclists - Staiano, W.; Marcora, S.; Romagnoli, M.; Kirk, U.; Ring, C. (Journal of Science and Medicine in Sport, 2023)
Objectives: To evaluate the effects of brain endurance training (BET) on endurance and cognitive performance in road cyclists.